Stokes Space Representation of Modal Dispersion - Ioannis Roudas; Jaroslaw Kwapisz (IEEE Photonics Journal, 2017)
Polarization-mode dispersion in single-mode fibers can be viewed as a special case of modal dispersion in multimode and multicore optical fibers. Exploiting the similarity between these two transmission effects, modal dispersion can be modeled in a way analogous to that of polarization-mode dispersion by modifying the conventional Jones–Stokes formalism. In this paper, we review the geometrical representation of modal dispersion in the generalized Stokes space by means of the modal dispersion vector. We summarize and unify the fundamental equations that encapsulate the properties of the modal dispersion vector. We prove that the modal dispersion vector can be expressed as a linear superposition of the Stokes vectors representing the principal modes. The coefficients of this expansion are the corresponding differential mode group delays. This concise and elegant expression can be considered as a simplified definition of the modal dispersion vector and can be used to facilitate analytical calculations.